Method for identifying chemically regenerated polyester

Through the cracking and high-efficiency capillary chromatography analysis of the polyester material to be tested, it is determined whether it is a chemically regenerated polyester, which solves the problem of difficulty in identifying native polyester and chemically regenerated polyester, and achieves accurate identification of polyester sources and fair distribution of subsidies.

CN119595766APending Publication Date: 2025-03-11ORIENTAL IND SUZHOU
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311744241.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively identify native polyester and chemically recycled polyester, which leads to some producers using native polyester as recycled polyester to obtain subsidies, resulting in economic losses.

Method used

By cracking the polyester material to be tested to form terephthalic acid (PTA), and using high-efficiency capillary chromatography to test the difference in content of p-methylbenzoic acid (p-Tol) in PTA, it is determined whether the polyester is a chemically regenerated polyester.

Benefits of technology

Accurate identification of polyester sources is achieved, fair distribution of subsidies is ensured, and transparency and reliability of the recycling process is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595766A_ABST
    Figure CN119595766A_ABST
Patent Text Reader

Abstract

The invention discloses an identification method of chemically regenerated polyester, which comprises the following steps: cracking a to-be-detected raw material, decomposing the to-be-detected raw material into small molecules and generating trace impurities, extracting the small molecules and the trace impurities, filtering, washing and drying to obtain a to-be-detected substance; analyzing the sample by adopting a high performance capillary chromatographic column, and judging whether the raw material to be detected is chemically regenerated polyester or not according to the content of trace impurities after cracking; the trace impurities comprise an organic impurity p-To l. According to the method, terephthalic acid and trace impurities are generated through high-temperature cracking, and the purpose of identification is achieved by utilizing the difference of the impurity content in the chemically regenerated polyester and the original polyester; the experiment verifies that the accuracy of identifying whether the raw materials are chemically regenerated or not can reach 100%, and the identification method is simple, efficient and high in accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester analysis, and in particular to an identification method for chemically regenerated polyester. Background Art

[0002] Virgin polyester (virgin PET) refers to a product synthesized by transesterification and polycondensation using terephthalic acid and ethylene glycol as monomers. It has excellent mechanical and thermal stability and is widely used in the production of various chemical products. With the increase in PET production, waste PET materials such as bottle flakes and discarded clothing have brought about environmental problems that cannot be ignored. In order to better solve waste pollution and achieve sustainable development, various countries have developed various ways to recycle waste PET, currently mainly physical recycling and chemical recycling methods.

[0003] The physical recycling method mainly recycles the waste PET materials by collecting, crushing and melting them into granules. The chemical recycling method decomposes PET into monomers through chemical reagents and repolymerizes them into polyester. The quality of the recycled polyester produced is comparable to that of polyester made from petroleum, while the energy consumption and carbon dioxide content are greatly reduced, which can realize the recycling of waste polyester and has good prospects. For this reason, all countries have corresponding policy support for the circular economy. However, for this reason, some producers try to pass off virgin polyester as recycled polyester to defraud subsidies and make profits. Therefore, there is an urgent need for corresponding identification methods for the source of polyester.

[0004] The difference between virgin polyester and chemically recycled polyester is that chemically recycled polyester undergoes a high-temperature cracking and refining process, which will produce small molecules and trace impurities after cracking. Chemically recycled polyester will absorb some trace impurities during the refining process, and the impurity content of the polyester material after polymerization will be reduced compared with virgin polyester. Therefore, this application designs a method for identifying chemically recycled polyester based on the above characteristics, and it is obviously of practical significance to judge whether the polyester is chemically recycled polyester based on the difference in impurity content between virgin polyester and chemically recycled polyester. Summary of the invention

[0005] The purpose of the present invention is to provide a method for identifying chemically recycled polyester, by cracking the polyester material to be tested to generate terephthalic acid (PTA), using high-performance capillary chromatography to test the difference in the content of p-toluic acid (p-Tol) in PTA, to determine whether the polyester is chemically recycled.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for identifying chemically regenerated polyester, comprising the following steps:

[0007] S1, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested;

[0008] S2, preparing a sample from the sample prepared in step S1, and analyzing the sample using a high-efficiency capillary column. The impurity content of the original polyester after pyrolysis is different from that of the chemically regenerated polyester after pyrolysis. The content of trace impurities after pyrolysis is used to determine whether the raw material to be tested is chemically regenerated polyester;

[0009] The trace impurities include the organic impurity p-toluic acid (p-Tol).

[0010] Preferably, the small molecule comprises PTA (terephthalic acid).

[0011] Preferably, the raw material to be tested in step S1 is prepared by chemical synthesis of polyester, and the raw materials used in the chemical synthesis include polyethylene terephthalate (BHET), dimethyl terephthalate (DMT), terephthalic acid (PTA), and ethylene glycol.

[0012] Preferably, the chemical synthesis method of the raw material to be tested specifically includes:

[0013] (1) rBHET synthesis method: the raw materials are reacted at 180°C to 250°C and 0.1 to 0.6 MPa for 6 to 8 hours, and 0.5% to 0.8% zinc acetate catalyst is added to obtain monomer BHET, which is washed with sufficient hot water for 3 to 5 times, and dried and collected, with a yield of more than 90%; the monomer BHET and ethylene glycol are added into a reactor at a mass ratio of 1:1.2 to 1.5, and antimony trioxide catalyst is added. Nitrogen is slowly introduced into the reactor to 0.1 to 0.4 MPa, and the temperature is raised to 200 to 250°C with stirring. After reacting for 2 to 4 hours, a PET melt is obtained; the PET melt enters cooling water to cool and solidify, and is sent to a pelletizer for slicing;

[0014] (2) rDMT synthesis method: the raw materials are heated at 180°C to 250°C, the mass ratio of methanol to PET feed is 2 to 3:1, and 0.5% to 0.8% manganese acetate catalyst is added at the same time, and the reaction is carried out for 6 to 8 hours to obtain monomer DMT, which is washed with sufficient hot water for 3 to 5 times, and dried and collected, with a yield of more than 95%; the monomer DMT and ethylene glycol are put into a reactor at a mass ratio of 1:1.2 to 1.8, and the catalyst antimony trioxide is added, and nitrogen is slowly introduced into the reactor to 0.1 to 0.4 MPa, and the temperature is raised to 210 to 250°C with stirring, and the reaction is carried out for 3 to 6 hours to obtain a PET melt; the melt enters cooling water to cool and solidify, and is sent to a pelletizer for slicing;

[0015] (3) rPTA synthesis method: The raw materials and sodium hydroxide are placed in a high-pressure reactor at a molar ratio of 1:3-5, pure water is added at a molar ratio of 10 times, the temperature is raised to 170°C for reaction for 2-4 hours, and PTA monomer is obtained. The monomer is washed with sufficient hot water for 3-5 times, and dried and collected. The yield is more than 92%. The PTA monomer and ethylene glycol are put into a reactor at a mass ratio of 1:1.2-1.8, antimony trioxide catalyst is added, nitrogen is slowly introduced into the reactor to 0.1-0.4MPa, the temperature is raised to 210-250°C with stirring, and the PET melt is obtained after reaction for 3-6 hours; the PET melt enters the cooling water for cooling and solidification, and is sent to the pelletizer for slicing.

[0016] Preferably, the cleavage in step S1 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cleavage temperature is 120-220° C., and the reaction time is 2-7 hours.

[0017] Preferably, the cracking in step S1 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.

[0018] Preferably, the cleavage in step S1 is performed by alkaline hydrolysis, and the water used in the alkaline hydrolysis is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.

[0019] Preferably, in step S1, the cracking reaction process further includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:1.

[0020] Preferably, the specific method of the alkaline alcoholysis method includes: adding the raw material to be tested, alcohol and catalyst into a three-necked flask in proportion, placing the three-necked flask in an oil bath heating device, installing a condensing reflux device, starting stirring, and the stirring rate is 500-1500rpm; cooling to 150°C after the reaction is completed and stopping stirring, replacing the mechanical stirring reflux device with a distillation device, reducing the pressure with a water pump, heating to evaporate the alcohol, and stopping heating after distilling until no distilled components are produced; during the reaction, when the system is heated to 130°C, bubbles can be seen to be generated, and the flask gradually becomes a white thick slurry.

[0021] Preferably, the reaction temperature of the alkaline alcoholysis method is 190° C. to 200° C., and the alcoholysis reaction time is 5 to 6 hours.

[0022] Preferably, the mass ratio of the raw material to be tested, the alcohol and the catalyst is 1:5-8:0.5-0.8.

[0023] Preferably, in step S1, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, and performing acid-base titration with dilute sulfuric acid to pH = 1.5 to 2.0 while stirring, and terminating the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.

[0024] Preferably, the temperature of the hot water is 85-95°C, preferably 90°C.

[0025] Preferably, the concentration of the dilute sulfuric acid is 0.4-0.6 mol / L.

[0026] Preferably, in step S2, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S1, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.

[0027] Preferably, in step S2, when a high-efficiency capillary chromatographic column is used to analyze the sample, the corresponding peak position of the chromatogram is that of the organic impurity p-Tol peak at 6.5 to 7.0 min.

[0028] Preferably, the inner diameter of the capillary is 60 μm to 80 μm, and the effective length is 50 cm to 70 cm.

[0029] Preferably, in step S2, the specific method for determining whether the raw material to be tested is chemically recycled polyester includes: if the content of organic impurity p-Tol is greater than 120 ppm, the raw material to be tested is virgin polyester; if the content of organic impurity p-Tol is less than 120 ppm, it can be determined that the raw material to be tested is chemically recycled polyester.

[0030] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0031] The invention generates terephthalic acid and trace impurities by high-temperature cracking, and achieves the purpose of identification by utilizing the difference in impurity content between chemically regenerated polyester and original polyester; the yield of the terephthalic acid product of the high-temperature cracking can reach 100%, and the purity can reach 98%. The organic impurities can be tested by a high-efficiency capillary electrophoresis method and the organic impurity content can be quantitatively calibrated. The experiment verifies that the accuracy of identifying whether the raw material is chemically regenerated can reach 100%, and the identification method is simple, efficient and highly accurate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, some of the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is the infrared spectra of the depolymerization product PTA and refined PTA;

[0034] Figure 2 This is a high performance capillary electrophoresis spectrum of the product of chemically regenerated polyester after alcoholysis of ethylene glycol in an embodiment;

[0035] Figure 3 The high performance capillary electrophoresis spectrum of the product of the original polyester after ethylene glycol alcoholysis in one embodiment. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The difference between virgin polyester and chemically recycled polyester is that chemically recycled polyester undergoes a high-temperature cracking and refining process, and will produce small molecules and impurities after depolymerization. The impurities include p-toluic acid (p-Tol), p-carboxybenzaldehyde (4CBA), and benzoic acid (BA); p-Tol plays an inhibitory role in the reaction, which will cause the molecular chain to lose activity and the chain end to be closed, thereby stopping the growth of molecular weight. Its existence directly affects the crystallization properties, molecular weight and distribution of polyester, thereby having an important impact on the intrinsic quality, spinnability and quality of polyester; by selecting at least 20 chemically recycled polyesters and at least 20 virgin polyesters as samples, the samples were subjected to high-temperature cracking, sample extraction, and high-efficiency capillary chromatography column analysis to obtain their p-Tol content, 4CBA content and BA content, and the p-To l content, 4CBA content and BA content were used as sample data, and the sample labels were input into the linear model for training. The training results show that when p-To l content, 4CBA content and BA content are less than 0. When the content of 1 is less than 120ppm, the raw material to be tested is chemically recycled polyester, and when the content of p-Tol is greater than 120ppm, the raw material to be tested is virgin polyester; however, neither 4CBA nor BA has a comparison rule. This is because p-Tol is easily soluble in hot water, and some of the impurities will be washed away by hot water; the p-Tol content of the chemically recycled polyester material after repolymerization will be lower than that of the virgin polyester.

[0038] Table 1 below shows the test results of some samples and the corresponding label table.

[0039] Table 1

[0040] Serial number p-Tol / ppm 4CBA / ppm BA / ppm Label 1 ≤150 ≤25 ≤30 Virgin polyester 2 156.2 5.6 87.9 Virgin polyester 3 174.8 7.8 230.2 Virgin polyester 4 166 9 812 Virgin polyester 5 167 5 477 Virgin polyester 6 166 9 812 Virgin polyester 7 175 0 279 Virgin polyester 8 139 0 369 Virgin polyester 9 175 0 279 Virgin polyester 10 139 0 369 Virgin polyester 11 167 5 477 Virgin polyester 12 82 0 66 Chemically recycled polyester 13 65 138 - Chemically recycled polyester 14 78 22 413 Chemically recycled polyester 15 64 1312 - Chemically recycled polyester 16 70 0 0 Chemically recycled polyester 17 77 0 0 Chemically recycled polyester 18 86 0 0 Chemically recycled polyester 19 76 30 1200 Chemically recycled polyester 20 59 308 65 Chemically recycled polyester 21 113 24 269 Chemically recycled polyester 22 96 27 487 Chemically recycled polyester 23 48 45 309 Chemically recycled polyester

[0041] Example 1

[0042] This embodiment discloses a method for identifying chemically regenerated polyester, comprising the following steps:

[0043] S 1. Polyester cracking: using ethylene glycol high temperature cracking method, the polyester to be tested is decomposed into small molecules and trace impurities.

[0044] Accurately weigh 30g of the polyester chips to be tested, add 150g of ethylene glycol and 18g of anhydrous sodium carbonate into a 500ml three-necked flask. Place the flask in a 190℃ oil bath heating device, install a condensation reflux device, start stirring, the stirring rate is 800rpm, and the reaction time is 6h;

[0045] When the system is heated to 130°C, bubbles can be seen, and the flask gradually turns into a white thick slurry. After the reaction is completed, cool to about 150°C and stop stirring. Change the mechanical stirring reflux device to a distillation device, reduce the pressure with a water pump, heat to evaporate ethylene glycol, and stop heating when there is no distilled component.

[0046] Add 300 ml of hot water at 90°C into the flask, stir to completely dissolve the solid; use a Buchner funnel to filter to remove insoluble matter, transfer the filtered solution to a 1000 ml beaker, and use 0.4 mol / L dilute sulfuric acid to perform acid-base titration to pH 1.5 while stirring, and then terminate the titration reaction; after filtering, wash and filter several times, place the filtered product in a 50°C oven to dry, and prepare the product for standby use;

[0047] S2, weigh 2.000±0.005g of the product in S1 and place it in a 100ml volumetric flask, use a pipette to transfer 3.3% ammonia water to ultrasonically dissolve the sample, filter to remove insoluble matter after dissolution, take the filtered solution and place it in a sample bottle to prepare a sample for later use; analyze the sample with a high-efficiency capillary column, and judge whether the polyester is recycled polyester based on the content of trace impurities after cleavage;

[0048] Furthermore, the high-efficiency capillary column analysis operating conditions are positive voltage mode, applied voltage is -15kV ~ +25kV, capillary inner diameter is 50mm, length is 60cm, automatic injection test, detection is performed with a UV detector, and external standard method is used for quantification. The high-efficiency capillary column analysis results are as follows Figure 3 shown.

[0049] Acid value test: weigh 1.5g sample into a 250ml conical flask, add 20ml dimethyl sulfoxide to dissolve, stir and dissolve, then add 20ml pure water. Add 0.1ml phenolphthalein indicator, and titrate with 0.5mol / L NaOH solution until pink.

[0050] The polyester to be tested in this embodiment adopts the rBHET synthesis method: the raw material is heated at 230°C and 0.3MPa for 6h, and 0.8% zinc acetate catalyst is added to obtain the monomer BHET, which is washed 5 times with sufficient hot water, dried and collected, and the yield reaches 93%. The monomer and ethylene glycol are put into the reactor at a mass ratio of 1:1.3, and the catalyst antimony trioxide is added. Nitrogen is slowly introduced into the reactor to 0.1-0.4MPa, and the temperature is raised to 240°C with stirring. After reacting for 3h, a PET melt is obtained. The melt enters the cooling water to cool and solidify, and is sent to the pelletizer for slicing.

[0051] Example 2

[0052] This embodiment discloses a method for identifying chemically regenerated polyester, comprising the following steps:

[0053] S1, polyester cracking, using ethylene glycol high temperature cracking method to decompose the polyester to be tested into small molecules and trace impurities;

[0054] Accurately weigh 30g of the polyester chips to be tested, add 150g of ethylene glycol and 18g of anhydrous sodium carbonate into a 500ml three-necked flask. Place the flask in a 190℃ oil bath heating device, install a condensation reflux device, start stirring, the stirring rate is 800rpm, and the reaction time is 6h;

[0055] When the system is heated to 130°C, bubbles can be seen, and the flask gradually turns into a white thick slurry. After the reaction is completed, cool to about 150°C and stop stirring. Change the mechanical stirring reflux device to a distillation device, reduce the pressure with a water pump, heat to evaporate ethylene glycol, and stop heating when there is no distilled component.

[0056] Add 300ml of hot water at 90℃ to the flask and stir to completely dissolve the solid. Use a Buchner funnel to filter and remove insoluble matter. Transfer the filtered solution to a 1000ml beaker and titrate with 0.4mol / L dilute sulfuric acid to pH 1.5 while stirring to end the titration reaction. After filtration, wash and filter several times, place the filtered product in a 50℃ oven to dry, and prepare the product for later use;

[0057] S2. Weigh 2.000±0.005g of the product in S1 and place it in a 100ml volumetric flask. Use a pipette to transfer 3.3% ammonia water to ultrasonically dissolve the sample. After dissolution, filter to remove insoluble matter, and place the filtered solution in a sample bottle to prepare a sample for later use. Use a high-efficiency capillary chromatographic column to analyze the sample, and determine whether the polyester is recycled polyester based on the content of trace impurities after cleavage.

[0058] Furthermore, the analysis operating conditions of the high-efficiency capillary column are in positive voltage mode, the applied voltage is -15kV to +25kV, the inner diameter of the capillary is 50mm, the length is 60cm, automatic injection test, detection with an ultraviolet detector, and quantification by external standard method.

[0059] Acid value test: weigh 1.5g sample into a 250ml conical flask, add 20ml dimethyl sulfoxide to dissolve, stir and dissolve, then add 20ml pure water. Add 0.1ml phenolphthalein indicator, and titrate with 0.5mol / L NaOH solution until pink.

[0060] The polyester to be tested in this embodiment adopts the rDMT synthesis method: the raw material is heated at 230°C for 6 hours, and 0.8% zinc acetate catalyst is added to obtain the monomer DMT, which is washed 5 times with sufficient hot water, dried and collected, and the yield reaches 96%. The monomer and ethylene glycol are put into the reactor at a mass ratio of 1:1.3, and the catalyst antimony trioxide is added. Nitrogen is slowly introduced into the reactor to 0.1-0.4MPa, and the temperature is raised to 240°C with stirring. After reacting for 3 hours, a PET melt is obtained. The melt enters the cooling water to cool and solidify, and is sent to the pelletizer for slicing.

[0061] Example 3

[0062] The embodiment of the present invention discloses a method for identifying chemically regenerated polyester, comprising the following steps:

[0063] S1, polyester cracking, using ethylene glycol high temperature cracking method to decompose the polyester to be tested into small molecules and trace impurities;

[0064] Accurately weigh 30g of the polyester chips to be tested, add 150g of ethylene glycol and 18g of anhydrous sodium carbonate into a 500ml three-necked flask. Place the flask in a 190℃ oil bath heating device, install a condensation reflux device, start stirring, the stirring rate is 800rpm, and the reaction time is 6h;

[0065] When the system is heated to 130°C, bubbles can be seen, and the flask gradually turns into a white thick slurry. After the reaction is completed, cool to about 150°C and stop stirring. Change the mechanical stirring reflux device to a distillation device, reduce the pressure with a water pump, heat to evaporate ethylene glycol, and stop heating when there is no distilled component.

[0066] Add 300 ml of hot water at 90°C into the flask, stir to completely dissolve the solid; use a Buchner funnel to filter to remove insoluble matter, transfer the filtered solution to a 1000 ml beaker, and use 0.4 mol / L dilute sulfuric acid to perform acid-base titration to pH 1.5 while stirring, and then terminate the titration reaction; after filtering, wash and filter several times, place the filtered product in a 50°C oven to dry, and prepare the product for standby use;

[0067] S2. Weigh 2.000±0.005g of the product in S1 and place it in a 100ml volumetric flask. Use a pipette to transfer 3.3% ammonia water to ultrasonically dissolve the sample. After dissolution, filter to remove insoluble matter, and place the filtered solution in a sample bottle to prepare a sample for later use. Use a high-efficiency capillary column for analysis to determine whether the polyester is recycled polyester based on the content of trace impurities after cleavage.

[0068] Furthermore, the analysis operating conditions of the high-efficiency capillary column are in positive voltage mode, the applied voltage is -15kV to +25kV, the inner diameter of the capillary is 50mm, the length is 60cm, automatic injection test, detection with an ultraviolet detector, and quantification by external standard method.

[0069] Further, acid value test: weigh 1.5g sample into a 250ml conical flask, add 20ml dimethyl sulfoxide to dissolve, stir to dissolve, then add 20ml pure water. Add 0.1ml phenolphthalein indicator, and titrate with 0.5mol / L NaOH solution until pink.

[0070] The polyester to be tested in this embodiment adopts the rPTA synthesis method: the raw material is reacted at 230°C and 0.3MPa for 4h, and 0.8% zinc acetate catalyst is added at the same time to obtain the monomer PET, which is washed 5 times with sufficient hot water, dried and collected, and the yield reaches 94%. The monomer and ethylene glycol are put into the reactor at a mass ratio of 1:1.3, and the catalyst antimony trioxide is added. Nitrogen is slowly introduced into the reactor to 0.4MPa, and the temperature is raised to 240°C with stirring. After reacting for 3h, a PET melt is obtained. The melt enters the cooling water to cool and solidify, and is sent to the pelletizer for slicing.

[0071] Example 4

[0072] The embodiment of the present invention discloses a method for identifying chemically regenerated polyester, comprising the following steps:

[0073] S1, polyester cracking, using ethylene glycol high temperature cracking method to decompose the polyester to be tested into small molecules and trace impurities;

[0074] Accurately weigh 30g of the polyester chips to be tested, add 150g of ethylene glycol and 18g of anhydrous sodium carbonate into a 500ml three-necked flask. Place the flask in a 190℃ oil bath heating device, install a condensation reflux device, start stirring, the stirring rate is 800rpm, and the reaction time is 6h;

[0075] When the system is heated to 130°C, bubbles can be seen, and the flask gradually turns into a white thick slurry. After the reaction is completed, cool to about 150°C and stop stirring. Change the mechanical stirring reflux device to a distillation device, reduce the pressure with a water pump, heat to evaporate ethylene glycol, and stop heating when there is no distilled component.

[0076] Add 300ml of hot water at 90℃ to the flask and stir to completely dissolve the solid. Use a Buchner funnel to filter and remove insoluble matter. Transfer the filtered solution to a 1000ml beaker and titrate with 0.4mol / L dilute sulfuric acid to pH 1.5 while stirring to end the titration reaction. After filtration, wash and filter several times, place the filtered product in a 50℃ oven to dry, and prepare the product for later use;

[0077] S2. Weigh 2.000±0.005g of the product in S1 and place it in a 100ml volumetric flask. Use a pipette to transfer 3.3% ammonia water to ultrasonically dissolve the sample. After dissolution, filter to remove insoluble matter, and place the filtered solution in a sample bottle to prepare a sample for later use. Use an efficient capillary column to analyze the sample, and determine whether the polyester is recycled polyester based on the content of trace impurities after cleavage.

[0078] Furthermore, the analysis operating conditions of the high-efficiency capillary column are in positive voltage mode, the applied voltage is -15kV to +25kV, the inner diameter of the capillary is 50mm, the length is 60cm, automatic injection test, detection with an ultraviolet detector, and quantification by external standard method.

[0079] Further, acid value test: weigh 1.5g sample into a 250ml conical flask, add 20ml dimethyl sulfoxide to dissolve, stir to dissolve, then add 20ml pure water. Add 0.1ml phenolphthalein indicator, and titrate with 0.5mol / L NaOH solution until pink.

[0080] The infrared spectrum test of the products of Examples 1-4 showed the following results: Figure 1As shown, with purified terephthalic acid as the blank control group, the peak position of the alcoholysis product is exactly the same as the blank, verifying that the alcoholysis product is terephthalic acid. The acid value test of the alcoholysis product and the p-Tol peak position and content test results are shown in the following table, and the product purity can reach more than 98%. For Examples 1 to 3, their p-Tol contents are all within 60 to 90 ppm, and they are all chemically recycled polyesters. For Example 4, its p-To l content is 150 to 160 ppm, which is a native polyester, which is consistent with the national standard test results of purified terephthalic acid.

[0081] p-Tol peak position min p-Tol content ppm Acid value mgKOH / g Example 1 6.90~6.96 76.3 672.8 Example 2 6.90~6.97 78.1 668.5 Example 3 6.91~6.97 82.0 662.5 Example 4 6.92~6.98 157.5 673.4

[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for identifying chemically regenerated polyester, characterized in that: The following steps are involved: S1, cracking the raw material to be tested, decomposing the raw material to be tested into small molecules and producing trace impurities, extracting the small molecules and trace impurities, filtering, washing, and drying to obtain the object to be tested; S2, preparing a sample from the sample prepared in step S1, and analyzing the sample using a high-efficiency capillary column. The impurity content of the original polyester after pyrolysis is different from that of the chemically regenerated polyester after pyrolysis. The content of trace impurities after pyrolysis is used to determine whether the raw material to be tested is chemically regenerated polyester; The trace impurities include the organic impurity p-toluic acid.

2. The identification method of chemically regenerated polyester according to claim 1, characterized in that: The raw material to be tested in step S1 is prepared by chemical synthesis of polyester, and the raw materials used in the chemical synthesis include ethylene terephthalate, dimethyl terephthalate, terephthalic acid, and ethylene glycol.

3. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: The cracking in step S1 is carried out by alkaline alcoholysis or alkaline hydrolysis, the cracking temperature is 120-220° C., and the reaction time is 2-7 hours.

4. The method for identifying chemically regenerated polyester according to claim 3, characterized in that: The cracking in step S1 adopts alkaline alcoholysis method, the alcohol used in the alkaline alcoholysis method is methanol or ethylene glycol, and the mass ratio of the raw material to be tested to the alcohol is 1:3-7.

5. The method for identifying chemically regenerated polyester according to claim 3, characterized in that: The cracking in step S1 adopts alkaline hydrolysis method, and the water used in the alkaline hydrolysis method is deionized water; the mass ratio of the raw material to be tested to water is 1:3-7.

6. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: In step S1, the cracking reaction process also includes adding a catalyst, the catalyst includes sodium carbonate, and the mass ratio of the catalyst to the raw material to be tested is 0.5 to 1:

1.

7. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: In step S1, the preparation method of the analyte includes: after the cleavage reaction is completed, hot water is added to the reaction container, stirring to completely dissolve the solid in the reaction container, filtering to remove insoluble matter, transferring the filtered solution to a beaker, stirring while performing acid-base titration with dilute sulfuric acid to pH = 1.5-2.0, and ending the titration reaction; after multiple filtration and washing, placing it in an oven to dry, the analyte can be obtained.

8. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: In step S2, the specific method of preparing the test object prepared in step S1 into a sample includes: adding ammonia water to the test object prepared in step S1, ultrasonically dissolving it, filtering it after dissolution to remove insoluble matter, and placing the filtrate in a sample bottle to prepare the sample.

9. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: In step S2, when a high-efficiency capillary column is used to analyze the sample, the corresponding peak position of the chromatogram is that the peak position of the organic impurity p-toluic acid peak on the chromatogram is between 6.5 and 7.0 min.

10. The method for identifying chemically regenerated polyester according to claim 1, characterized in that: In step S2, the specific method for determining whether the raw material to be tested is chemically recycled polyester includes: if the content of p-toluic acid as an organic impurity is greater than 120 ppm, the raw material to be tested is virgin polyester; if the content of p-toluic acid as an organic impurity is less than 120 ppm, it can be determined that the raw material to be tested is chemically recycled polyester.

Citation Information

Cited By

  • Screening method for regenerating PET (polyethylene terephthalate) and PTA (pure terephthalic acid) by chemical or enzymatic method

    CN121476462A